Assessment of organic matter content in basalt soils under cultivation of major crops in Dak Lak province - Anh, Luu The; Thuy, Nguyen Thi; Thanh, Nguyen Duc; Nam, Hoang Quoc (Vietnam Journal of Earth Sciences, 2015)
The content of soil organic matters (SOM) plays an important role in natural fertility and crop nutrition. SOM is strongly transformed by impacts of the high temperature and humidity regime of monsoon tropical conditions, and cultivation activities. The soils which were derived from basalt weathering products in Dak Lak province, of about 344.977 ha; almost of the area of basalt soils has been exploited to grow perennial crops (such as coffee, rubber, pepper, etc.,). After long time of the intensive perennial crop cultivation, the organic matter content of basalt soils has already been degraded significantly. At the same time, the ferralization and mineralization processes usually create acidic environment and poor nutrient of basalt soils. The findings of the study shown that, organic matter content of basalt soils in the top layer is from 1,74 to 6,43%; and dramatically decrease in the deep soil horizons. The volume of organic matter in the depth of 0 - 20 cm and 0 - 100 cm ranges from 40,90 to 110,55 tons ha-1 and from 103,71 to 332,03 tons ha-1, respectively. Ratio C/N is low due to the poor rate of decomposition of the organic compounds and nitrogen supply availability from humus. References Lưu Thế Anh, 2012: Nghiên cứu xây dựng bản đồ thoái hóa đất tỉnh Đắk Lắk và Đắk Nông phục vụ sử dụng bền vững tài nguyên đất. Luận án tiến sỹ Địa lý. Tài liệu lưu trữ tại Viện Địa lý, Hà Nội, 145tr. Đỗ Ánh, 2003: Độ phì nhiêu của đất và dinh dưỡng cây trồng. Nhà xuất bản Nông nghiệp, Hà Nội, 83tr. Tôn Thất Chiểu, Lê Thái Bạt, Nguyễn Khang, Nguyễn Văn Tân, 1999: Sổ tay điều tra phân loại đánh giá đất. Nhà xuất bản Nông nghiệp, Hà Nội, 175tr. Nguyễn Xuân Cự, 2005: Thành phần và tính chất đặc trưng của chất hữu cơ trong một số loại đất ở Việt Nam. Tạp chí Khoa học Đất, T.21, tr.21-26. Phan Liêu, 1985: Hàm lượng mùn và chiều hướng tiến hóa của chất hữu cơ trong đất cát biển. Tuyển tập các công trình nghiên cứu khoa học và kỹ thuật nông nghiệp 1981-1985. Nhà xuất bản Nông nghiệp, Hà Nội, tr.175-177. Nguyễn Tử Siêm, 1999: Tuần hoàn chất hữu cơ - Những đóng góp cho nền nông nghiệp sinh thái hài hòa ở Việt Nam. Kết quả nghiên cứu khoa học, quyển 3. Nhà xuất bản Nông nghiệp, Hà Nội, tr.121-138. Nguyễn Hữu Thành, Phạm Thế Anh, Nguyễn Tiến Sỹ, 2009: Nghiên cứu trạng thái mùn trong đất đỏ phát triển trên đá basalt trồng cà phê tỉnh Đắk Nông. Tạp chí Khoa học và Phát triển, Trường Đại học Nông nghiệp Hà Nội, số 4, tr.491-499. Đỗ Đình Sâm và Nguyễn Ngọc Bình, 2000: Đánh giá tiềm năng sản xuất đất lâm nghiệp Việt Nam. Nhà xuất bản Nông nghiệp, Hà Nội. Nguyễn Văn Toàn, 2005: Giải pháp tổng thể sử dụng hợp lý và bảo vệ đất basalt Tây Nguyên. Nhà xuất bản Nông nghiệp, Hà Nội, 316tr. Nguyễn Vy, 2003: Độ phì nhiêu thực tế. Nhà xuất bản Nghệ An, Tp. Vinh, 148tr. Birch, H.F. and Friend, M.T., 1956: The organ matter and nitrogen status of east African soils. Journal of Soil Science, Vol. 7(1), 156-167. Tilahun Chibsa and Asefa Ta, A., 2009: Assessment of soil organic matter under four land use systems in the major soils of Bale highlands, South East Ethiopia. Factors affecting soil organic matter distribution. World Applied Sciences Journal 6 (11), 1506-1512. Kalbitz, K., 2001: Properties of organic matter in soil solution in a German fen area as dependent on land use and depth. Geoderma 104, 203-214. Orlov, D.S., 1992: Soil chemistry. Taylor & Francis Group, New York, America, 390 pp. Siderius, W., 1992: Soil derived land qualities. International Institute for Aerospace Survey and Earth Sciences, SOL. 48, Wageningen, the Netherlands, 37-84. Solomon, D., Lehmann, J., Tekalign, M.F., Fritzsche and Zech, W., 2001: Sulfur fractions in particle-size separates of the sub-humid Ethiopian highlands as influenced by land use changes. Geoderma 102, 41-59.